2012
DOI: 10.1162/jocn_a_00148
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Interactions between Lexical Semantic and Word Form Analysis during Word Recognition in Context: Evidence from ERPs

Abstract: Abstract■ We used ERPs to investigate the time course of interactions between lexical semantic and sublexical visual word form processing during word recognition. Participants read sentenceembedded pseudowords that orthographically resembled a contextually supported real word (e.g., "She measured the flour so she could bake a ceke…") or did not (e.g., "She measured the flour so she could bake a tont…") along with nonword consonant strings (e.g., "She measured the flour so she could bake a srdt…"). Pseudowords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
77
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 52 publications
19
77
3
Order By: Relevance
“…Newman and Connolly (2004) and Vissers, Chwilla, and Kolk (2006) found that pseudohomophones that were orthographically similar to highly predictable words (e.g., bouks for the predictable books) elicited larger LPCs than predictable words, but pseudohomophones that were orthographically similar to unpredictable words did not. Similarly, Laszlo and Federmeier (2009) and Kim and Lai (2012) reported a post-N400 LPC effect for pseudowords that were orthographically similar to the predicted words. Along with Vissers et al (2006), both sets of authors interpreted the effect as a detection of a conflict between predicted and actually encountered words.…”
Section: Predicting Formmentioning
confidence: 69%
See 3 more Smart Citations
“…Newman and Connolly (2004) and Vissers, Chwilla, and Kolk (2006) found that pseudohomophones that were orthographically similar to highly predictable words (e.g., bouks for the predictable books) elicited larger LPCs than predictable words, but pseudohomophones that were orthographically similar to unpredictable words did not. Similarly, Laszlo and Federmeier (2009) and Kim and Lai (2012) reported a post-N400 LPC effect for pseudowords that were orthographically similar to the predicted words. Along with Vissers et al (2006), both sets of authors interpreted the effect as a detection of a conflict between predicted and actually encountered words.…”
Section: Predicting Formmentioning
confidence: 69%
“…1. We used only the posterior channels, where, consistent with the findings in previous literature (e.g., Kim & Lai, 2012;Laszlo & Federmeier, 2009), N400 and LPC effects had been maximal. For the semantic prediction reduced-N400 effect, we tested the effect of cloze value on the crucial difference between the semantic condition and the unrelated condition.…”
Section: Effects Of Cloze Probabilitymentioning
confidence: 91%
See 2 more Smart Citations
“…For example, listeners are more likely to direct their eye-gaze to a picture of an edible object (e.g., a cake) when they hear the beginning of an utterance like 'The boy will eat…' compared to a neutral utterance such as 'The boy will move…' (Altmann & Kamide, 1999). Further, much evidence has suggested that comprehenders compute rich expectations about upcoming inputs at multiple levels of representation (syntactic: Ilkin & Sturt, 2011;Lau, Stroud, Plesch, & Phillips, 2006;Levy, Fedorenko, Breen, & Gibson, 2012;Omaki et al, 2015;Staub & Clifton, 2006;Wicha et al, 2004;Van Berkum et al, 2005;Yoshida, Dickey, & Sturt, 2013;lexico-semantic: Federmeier & Kutas, 1999;Kutas & Hillyard, 1984;Otten & Van Berkum, 2008;Szewczyk & Schriefers, 2013; phonological and orthographic: Delong et al, 2005;Dikker, Rabagliati, Farmer, & Pylkkanen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009;Farmer, Yan, Bicknell, & Tanenhaus, 2015;Kim & Lai, 2012;Laszlo & Federmeier, 2009). Here, we operationally define 'prediction' as the pre-activation of stored representations before the bottom-up input is encountered, and we will make no a priori assumptions regarding the nature of the mechanisms involved (e.g., whether they are automatic or controlled).…”
Section: Prediction In Language Comprehensionmentioning
confidence: 99%